2011
DOI: 10.1007/s00216-011-4875-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of real-time PCR screening methods for detection of cry1A.105 and cry2Ab2 genes in genetically modified organisms

Abstract: Primers and probes were developed for the element-specific detection of cry1A.105 and cry2Ab2 genes, based on their DNA sequence as present in GM maize MON89034. Cry genes are present in many genetically modified (GM) plants and they are important targets for developing GMO element-specific detection methods. Element-specific methods can be of use to screen for the presence of GMOs in food and feed supply chains. Moreover, a combination of GMO elements may indicate the potential presence of unapproved GMOs (UG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 27 publications
(30 reference statements)
1
34
0
1
Order By: Relevance
“…Two GM crop cultivars carrying the VT PRO event (BM 915 PRO and SHS 7920 PRO) presented positive results for all three targets. Furthermore, the other conventional and GM maize cultivars presented results that were expected based on register information, as demonstrated in previous studies (Reiting et al, 2007;Waiblinger et al, 2008;Dinon et al, 2011;Huber et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Two GM crop cultivars carrying the VT PRO event (BM 915 PRO and SHS 7920 PRO) presented positive results for all three targets. Furthermore, the other conventional and GM maize cultivars presented results that were expected based on register information, as demonstrated in previous studies (Reiting et al, 2007;Waiblinger et al, 2008;Dinon et al, 2011;Huber et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Although requiring special reagents and equipment, PCR can detect the presence of specific exogenous genes inserted into the plant genome (including the seeds), and represents the most widely used method to detect GM food and feed (Dinon et al, 2011;Branquinho et al, 2013;Cantelmo et al, 2013). In the present study, we used real time PCR to detect three GM-specific fragments: the promoter region p-35S derived from the cauliflower mosaic virus (Waiblinger et al, 2008;Huber et al, 2013), the terminator region, t-Nos, derived from the nopaline synthase gene of Agrobacterium tumefaciens (Reiting et al, 2007;Huber et al, 2013), and the main cry1A.105 gene from Bt (Dinon et al, 2011). These PCR assays were successfully implemented, in addition to an assay targeting the constitutive hmg gene, which was used as an endogenous control (Corbisier et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D€ orries, Remus, Gr€ onewald, Gr€ onewald, and Berghof-J€ ager (2010) developed a multiplex real-time PCR kit to detect P-35S, T-nos, P-FMV, and the bar gene for GMO screening purposes. Grohmann, BrunenNieweler, Nemeth, and Waiblinger (2009) and Dinon et al (2011) reported screening methods that targeted cording genes with herbicide tolerance and insect resistance. Randhawa, Chhabra, and Singh (2009) established a multiplex PCR system that targeted selectable markers and reporter genes for GMO screening.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, additional detection methods are sometimes necessary in order to target specific (groups of) GMOs. Some recent examples of additional qPCR screening methods are the element bar and construct ctp2/cp4epsps [21], the elements cry1A.105 and cry2Ab2 [15], promoters P-FMV, P-nos, P-SSuAra, P-TA29, P-ubi, P-rice actin and terminators T-35S, T-E9, T-ocs, T-g7 [14], element vip3A [29], and element cry1Ab/Ac and construct P-ubi/cry [22]. Recent examples of SYBR ® Green detection methods are P-nos and P-FMV [9], cry3Bb and gat/T-pinII [10], and the application of Combinatory SYBR ® Green PCR Screening (CoSYPS) [4,30,42].…”
mentioning
confidence: 99%